Quality Parameters of Wort Produced with Lentil Malt with the Use of Some Enzymatic Preparations - Katarzyna Fulara; Aneta Ciosek; Olga Hrabia; Monika Cioch-Skoneczny; Krystian Klimczak; Aleksander Poreda (Foods)
Lentils represent a promising alternative for beer production, potentially offering unique benefits and challenges. This study investigates the physicochemical properties of brewer’s wort derived from both barley and lentil grains. Specifically, it compares worts produced from raw and malted lentils, with and without the addition of amylase and protease enzymes. Key parameters such as filtration and saccharification times, pH, extract content, color, turbidity, polyphenol content, free amino nitrogen (FAN), nitrogen content, and metal ion and sugar composition were meticulously measured. Results indicate that both raw and malted lentils can be utilized to produce brewer’s wort, with the malting process enhancing extract levels. Notably, the addition of amylolytic enzymes resulted in the highest extract levels for both lentil types. Lentil-based worts exhibited significantly higher FAN levels and lower turbidity compared to barley malt worts. Despite barley malt’s established advantages in saccharification efficiency, filtration, and extract yield, lentils offer distinct benefits such as elevated FAN levels and unique color profiles. Enzyme treatments play a crucial role in optimizing lentil-based wort production, highlighting the potential for lentils in brewing applications.